A Study on Customer Preference and Satisfaction towards KTM Bike in Coimbatore City - Amuthanayaki, Dr VP; Kodhainayaki, N (Journal of Advanced Research in HR and Organizational Management, 2022)
KTM India most trusted two-wheeler automobile company launched Duke200 in 2008. This study was conducted in Coimbatore city where over the years; craze of two wheeler has improved a lot. Firstly people used to prefer scooter, rather than bikes because they use to say, it is also a gear vehicle good mileage and more importantly we have space to keep some articles in front of it but in bikes there is no such provision. The Euro emission norms led the existing players in to two stroke segment to install catalytic converter. All the new models are now being replaced by 4-stroke motorcycle. Excise duty on motorcycles has been reduced resulting in price reduction, while has aided in propelling the demand for motorcycle.